The Era of Rhythm Control: A Review of the Epidemiology and Clinical Impact of Anti-Arrhythmic Medications in Atrial Fibrillation - Cicely Anne Dye; Jamario Skeete; Asad Khan; Michael Dunleavy; Michael Dietrich; Annabelle Santos Volgman; Parikshit Sharma; Henry Huang (MDPI AG, 2023)
Atrial fibrillation has been described as a global epidemic with a three-fold increase in prevalence in the last 50 years. As the prevalence of atrial fibrillation continues to grow, multiple landmark trials have been designed to determine the best method to treat atrial fibrillation. Initial trials have stated that rate control was not inferior to rhythm control, however, as the efficacy of rhythm control of atrial fibrillation has improved, a benefit in rhythm control has been shown. Because of this trend towards increased rhythm control, more patients have been placed on anti-arrhythmic medications. This paper will review the epidemiology and clinical impact of the utilization of anti-arrhythmic medications. As we enter the era of rhythm control, increased awareness is needed regarding the monitoring and potential adverse events that can occur with these medications. Providers must balance the increased emphasis on rhythm control with the overall clinical impact on their patients due to drug-to-drug interactions and adverse effects that can occur with different co-morbidities. If the clinical momentum towards rhythm control continues, real-world data analysis will be needed to evaluate the clinical impact of the use, risk, and benefits of anti-arrhythmic medications.